Behavioral and neuro-functional consequences of eliminating the KCNQ3 GABA binding site in mice - Chen, Kiki J.; Yoshimura, Ryan; Edmundo, Clarissa Adriana; Truong, Tri Minh; Civelli, Olivier; Alachkar, Amal; Abbott, Geoffrey W. (Frontiers in Molecular Neuroscience, 2023)
Voltage-gated potassium (Kv) channels formed by α subunits KCNQ2-5 are important in regulating neuronal excitability. We previously found that GABA directly binds to and activates channels containing KCNQ3, challenging the traditional understanding of inhibitory neurotransmission. To investigate the functional significance and behavioral role of this direct interaction, mice with a mutated KCNQ3 GABA binding site (Kcnq3-W266L) were generated and subjected to behavioral studies. Kcnq3-W266L mice exhibited distinctive behavioral phenotypes, of which reduced nociceptive and stress responses were profound and sex-specific. In female Kcnq3-W266L mice, the phenotype was shifted towards more nociceptive effects, while in male Kcnq3-W266L mice, it was shifted towards the stress response. In addition, female Kcnq3-W266L mice exhibited lower motor activity and reduced working spatial memory. The neuronal activity in the lateral habenula and visual cortex was altered in the female Kcnq3-W266L mice, suggesting that GABAergic activation of KCNQ3 in these regions may play a role in the regulation of the responses. Given the known overlap between the nociceptive and stress brain circuits, our data provide new insights into a sex-dependent role of KCNQ3 in regulating neural circuits involved in nociception and stress, via its GABA binding site. These findings identify new targets for effective treatments for neurological and psychiatric conditions such as pain and anxiety.